Parental Knowledge, Practices and Cultural Perceptions Regarding Infant Sunlight Exposure: A Cross- Sectional Study - KABIR, MALIK MUHAMMAD; SHAHID, ABDUL REHMAN; KHAN, MUHAMMAD WALLEED; SAEED, HAFIZA HUMA; MALIK, NAWAL; TARIQ, URFA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Sunlight exposure plays a critical role in the synthesis of vitamin D, essential for bone development and overall health in infants. Despite its importance, cultural beliefs, lack of awareness, and unsafe exposure practices may hinder appropriate utilization. This study investigates parental knowledge, practices, and cultural perceptions regarding infant sunlight exposure in a semi-urban Pakistani setting. Objective: To evaluate parental knowledge, practices, and sociocultural factors influencing sunlight exposure in infants at POF Hospital Wah Cantt. Methods: A cross-sectional study was conducted over four months involving 100 parents of infants aged 1 to 6 months. Data were collected through a structured questionnaire covering demographics, exposure practices, beliefs, and perceived benefits or harms of sun exposure. Descriptive statistics were computed using SPSS version 21. Results: Among participants, 73% regularly exposed their infants to sunlight, with 69% doing so daily. Most preferred morning exposure (70%). Although 65% were aware of vitamin D benefits, only 35% used sunscreen. Cultural concerns like skin darkening (31%) and illness fear (21%) were common barriers. Conclusion: While general awareness about sunlight benefits was observed, unsafe practices and cultural misconceptions remain prevalent. Targeted education addressing these gaps is necessary to improve infant health outcomes.